Ngarakantuntja = Chasing kangaroo - Tjilari, Andy.; Institute for Aboriginal Development (Alice Springs, N.T.) (Alice Springs : Institute for Aboriginal Development, 1974)
Narrative; with English text.
Pitjantjatjara text with parallel English translation.
Keywords: Pitjantjatjara language -- Readers; Pitjantjatjara language -- Text-books for foreign speakers -- English; Pitjantjatjara people (C6) (NT SG52-11); Pitjantjatjara language (C6) (NT SG52-11); Education - Language - Indigenous languages; Hunting - Kangaroo / Wallaby; Pintupi language (C10) (NT SF52-11); Stories and motifs - Kangaroos / Wallabies; South Australia - Central Australia (SA SG52, SG53); Northern Territory (NT)